The Covid 19 And The Likes Of Possible Pandemic: An Islamic Way To Earnest Prophylaxis - Muhammad Dare Garba; Yusuf Olawale Owa-Onire Uthman (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
This paper, examines the Covid 19 pandemic and its future predictable like the deadly influenza virus, showcasing the Islamic-social measures to deal with such viruses with references to its events in history. The research traced back centuries in the history of the world to identify similar case studies. In the history of humans, there is Hong Kong/68 (H3N2) pandemic, and when the Russian contagious disease strain (HINI) resurfaced in 1977, the contagious disease family originated from mammals and several other animals. Hence, the study established the fact that Islam prescribes different measures to contain it. Muslim folks and others should take good care of their health by eating a balanced diet and maintaining good health habits in their bodies and places of worship. Descriptive and doctrinal methods are adopted to explain the Islamic perspective and some social strategies for dealing with pandemics. Finally, it is recommended that the provision provided in the Islamic objective before the secular policy and development programs should be correctly implemented to save lives, even prior to disease challenges. While Muslims are also urged to understand their religion and every human should be a law-abiding citizen to tackle the menace of pandemics around the world.